Synopsis of Akamboja (Coleoptera: Phengodidae): new species, synonym, new records and remarks on abdominal morphology for the genus - Coelho, Matheus A. F.; Mermudes, José Ricardo M.; Roza, André Silva (Zootaxa, 2024)
Akamboja Roza et al., 2017 (Phengodidae: Mastinocerinae) was described to include five species, all from Atlantic Forest, which are characterized by having ten segmented antennae, biflabellate from antennomeres IV-VIII, and with fused flabellae on antennomere IX. The genus comprises six species today, including one from Ilha Grande (Angra dos Reis, Rio de Janeiro State, Brazil) with the IX antennomere flabellae not fused. In this paper, we describe seven new species based on specimens from seven entomological collections: Akamboja ganhoae sp. nov., Akamboja kumagaiae sp. nov., Akamboja microphthalmus sp. nov., Akamboja peckorum sp. nov., Akamboja piauiensis sp. nov., Akamboja planautensis sp. nov., and Akamboja wittmeri sp. nov. These new species include new biome records for Brazil (Cerrado, Caatinga and Amazonia), and the first species of the genus from Venezuela and Argentina. The seven new species fit in the genus diagnosis, but presents an antennal morphological variation in the flabellae of the antennomere VIII-IX: fusion of flabellae in antennomeres IX, in both antennomeres VIII and IX, or the absence of any fusion in any flabellae. Based on this variation, we propose an updated diagnosis for the genus. We also discuss and propose Akamboja caparaoensis Roza et al., 2017 as a new junior synonym of Akamboja cleidae Roza et al., 2017, and provide new distributional records for A. minimum Roza et al., 2017 and A. insularis Roza et al., 2018. Additionally, we describe for the first time in the genus the abdominal membranous projection present in several Mastinocerinae, but previously ignored, as well as the morphology of tergites IX, and X, and sternite IX.